CRITICAL ANALYSIS ON THE PRACTICE AND EFFECTIVENESS OF DIGITAL MARKETING STRATEGIES IN STRENGTHENING MSME BRANDING IN KENDARI CITY - Bunga Kartika; Muh. Husriadi; La Ode Ahmad Darwin (CV. Adiba Aisha Amira, 2026)
Kendari City's MSMEs, which contribute 60% of local GDP, are facing the challenge of low brand equity due to fragmented digital marketing strategies and weak digital infrastructure in the era of transformation post-pandemic. This study aims analyze critical the practice and effectiveness of digital marketing strategies in strengthening the branding of Kendari MSMEs using a qualitative approach descriptive. Data collected through interview In-depth research with 15 informants (MSME owners, agencies, Cooperative Service officials), observation, and documentation, analyzed using the Miles & Huberman model. The results identified three theme Main factors: strategic fragmentation (80%), cultural-content gap Tolaki (73%), and digital infrastructure bottleneck (93%), hindering the RACE framework and brand associations Aaker (1991). Implications covers training local cultural content and contribute to the marketing roadmap contextual emerging market Indonesia.